Prevalence of ESBL Producing and Carbapenem-resistant E. Coli in Urinary Tract Infection from Tertiary Care Hospital - Khan, Zahid Ullah; Taqweem Ul Haq; Ahmad, Jamil; Abdullah; Rahim Ullah; Khattak, Anila Rasheed (Indus Journal of Bioscience Research, 2025)
Background: Urinary tract infections are the most common kind of nosocomial infection. E. coli is the leading cause of UTIs and show resistance to carbapenem. Objective: The aim of this study was to determine the Prevalence of ESBL Producing and carbapenem-resistant E. coli in urinary tract infection from tertiary care hospital. Material and Method: The present cross sectional study was conducted at the d Institute of Kidney Diseases Hayatabad Peshawar after taking permission from the ethical board of the institute. A total of 324 mid-stream urine samples were collected in sterile, closed containers from patients presenting with UTI complications. Culturing was done on standard laboratory techniques. Gram staining, microscopy, and biochemical testing were used to identify and confirm the presence of Escherichia coli. The Kirby-Bauer disc diffusion technique was used on Mueller-Hinton agar to determine antibiotic susceptibility. For screening purposes of ESBL generation, E. coli isolates were tested for resistance to cephalosporin and/or aztreonam. A crucial hole or shoulder zone formed by the combination of amoxicillin, clavulanic acid, and one of the surrounding cephalosporin or azitreonam was identified as an ESBL producer. E. coli strains resistant to imipenem, meropenem, or both were designated carbapenem-resistant. Data was analyzed using SPSS version 21 and presented in the tables and figures. Results: A total of 324 urine samples were processed out of which 260 (80.2%) showed bacterial growth. UTIs were most common in female 140(53.8%) as compared to male 120(46.1%) . Out of the total culture positive, the most prevalent uropathogen was E.coli 150(57.6%) followed by Klebsiella 60(23%, Proteus 26(10%) and Pseudomonas species 24(9.2%) correspondingly The E.coli isolates were sensitive to Meropenum 95%,Imepenem 94%,amikacin 89% , Fosfomycine 88% and Nitrofurantoin 72% while exhibited the highest resistance to ampicillin (88%), followed by ofloxacin 70%, ciprofloxacin 65%, ceftriaxone 65%, and co-trimoxazole 64% . Out of the total 150 E.coli bacteria 100(66.6%) were extended spectrum β - lactamases producers and 50(33.3%) were not producers. Among ESBL isolates 10(6.6%) were carbapenem resistant and 4(2.6%) were carbapenem-resistant but not ESBL producers. Conclusion: The current study reported high prevalence of ESBL-producing E. coli, but carbapenem-resistant E. coli was less prevalent in urinary tract infections.